Ruminal degradability and fecal digestibility of hydroponic fresh forage of maize (Zea mays) in domestic goats in Santa Elena, Ecuador - Acosta, N.; Lima, R.; Avellaneda, J.; Mirabá, C. (Cuban Journal of Agricultural Science, 2016)
Dry matter, organic matter and crude protein degradability and digestibility were assessed in hydroponic fresh forage hay of maize, cultivated with three nutritive solutions (Hoagland, La Molina and FAO)at 12 d of harvested. The experiment was developed from July to September, 2014 at “La Sevilla” farm located in San Marcos commune, canton and province of Santa Elena, Ecuador. Eight domestic goats were used (four fistulae fitted and without fistulae) which were adapted to the feed for 14d. For determining ruminal degradability and fecal digestibility, 5 g of each sample were introduced in the rumen in nylon bags (45 – 50 μm) and at 0, 3, 6, 9, 12, 24, 48 and 72 h were assessed. Later they were removed and washed until attaining crystalline water and the bromatological analyses were carried out. Ruminal degradation parameters showed high levels of dry matter, organic matter and crude protein degradability. Results evidence that there were no differences in the degradability parameters for dry and organic matter which was demonstrated by the forage produced through different nutritive solutions. On evaluating the effect ofthe nutritive solution on the degradability parameters of the crude protein of the hydroponic fresh forage of maize, the “a” fraction and the effective rumen degradation with the FAO and Hoagland solutions were higher (P < 0.05) regarding that obtained with the solution La Molina. It is concluded that the hydroponic fresh forage of maize cultivated with three nutritive solutions exhibited high levels of degradability and fecal digestibility of the dry mater, organic matter and crude protein in goats. However, results offecal digestibility of the nutrients studied show that the Hoagland and FAO solutions are the most promissory for producing this forage in the studied region.Key words: degradability, digestibility, hydroponic fresh forage of maize